Antioxidative Activities and Polyphenolic Content of Different Varieties of Malaysian Young Corn Ear and Cornsilk. (Aktiviti Antioksida dan Kandungan Polifenolik bagi Varieti Berbeza Jagung Muda dan Sutera Jagung Malaysia) - Ho, Y. M.; Nizam, Wan Amir; Wan Rosli, W. I. (Faculty of Science and Technology, Universiti Kebangsaan Malaysia, 2016)
This study aimed to determine the antioxidant capacity, total polyphenolic and total flavonoid content of Malaysian young corn ear (YCE) and its cornsilk (CS) of different varieties. Three different varieties of YCE and its CS locally grown in Malaysia were chosen namely Big Fruit, Thai Supersweet and Bi-color. CS Bi-color displayed the highest total phenolic content (143.58 mg GAE/g extract) while CS Thai Supersweet exhibited the highest total flavonoid content (26.63 mg CAE/g extract). Meanwhile, YCE of Bi-color variety demonstrated the highest total polyphenolic and flavonoid content (92.64 and 18.14 mg CAE/g extract, respectively) compared to other YCE varieties. At 800 μg/mL, CS of Bi-color (93.82%) recorded the strongest electron donor due to higher DPPH scavenging activity, followed by CS Thai Supersweet (92.87%), YCE Bi-color (41.94%), YCE Thai Supersweet (28.87%), CS Big Fruit (28.87%) and YCE Big Fruit (21.38%). For FRAP, CS of Bi-color showed the highest reducing power activity (65.46%) among all the crude extracts. There is a significant correlation between total polyphenolic content, DPPH free radical scavenging activity and FRAP of YCE and CS of different varieties. In summary, CS extracts are the potential ingredient to be applied in food industries and at the same time reducing agriculture wastage. || Kajian ini bertujuan menentukan kapasiti antioksidan, kandungan jumlah polifenolik dan flavonoid dalam varieti berbeza jagung muda (YCE) dan sutera jagung (CS) Malaysia. Tiga varieti berbeza YCE dan CS yang ditanam di Malaysia telah dipilih iaitu Big Fruit, Thai Supersweet dan Bi-color. CS Bi-color menunjukkan kandungan jumlah polifenol paling tinggi (143.58 mg GAE/g ekstrak) manakala CS Thai Supersweet menunjukkan kandungan jumlah flavonoid yang tertinggi (26.63 mg CAE/g ekstrak). Sementara itu, YCE varieti Bi-color menunjukkan kandungan jumlah polifenol dan flavonoid tertinggi (masing-masing 92.64 dan 18.14 mg CAE/g ekstrak) berbanding varieti YCE yang lain. Pada 800 μg/mL, CS Bi-color (93.82%) merekodkan pendermaan elektron terkuat disebabkan aktiviti perencatan DPPH yang tinggi, diikuti oleh CS Thai Supersweet (92.87%), YCE Bi-color (41.94%), YCE Thai Supersweet (28.87%), CS Big Fruit (28.87%) dan YCE Big Fruit (21.38%). Untuk FRAP, CS Bi-color menunjukkan aktiviti kuasa penurunan paling tinggi (65.46%) antara semua ekstrak mentah. Terdapat korelasi signifikan antara kandungan jumlah polifenolik, perencatan radikal bebas DPPH dan FRAP bagi varieti berbeza YCE dan CS. Secara kesimpulannya, ekstrak CS berpotensi sebagai ramuan untuk diaplikasikan dalam industri makanan dan dalam masa yang sama dapat mengurangkan sisa pertanian.